Identifying cancer-associated leukocyte profiles using high-resolution flow cytometry screening and machine learning - Simon Davis, David A.; Ritchie, Melissa; Hammill, Dillon; Garrett, Jessica; Slater, Robert O.; Otoo, Naomi; Orlov, Anna; Gosling, Katharine; Price, Jason; Yip, Desmond; Jung, Kylie; Syed, Farhan M.; et al. (Frontiers in Immunology, 2023)
Machine learning (ML) is a valuable tool with the potential to aid clinical decision making. Adoption of ML to this end requires data that reliably correlates with the clinical outcome of interest; the advantage of ML is that it can model these correlations from complex multiparameter data sets that can be difficult to interpret conventionally. While currently available clinical data can be used in ML for this purpose, there exists the potential to discover new “biomarkers” that will enhance the effectiveness of ML in clinical decision making. Since the interaction of the immune system and cancer is a hallmark of tumour establishment and progression, one potential area for cancer biomarker discovery is through the investigation of cancer-related immune cell signatures. Hence, we hypothesise that blood immune cell signatures can act as a biomarker for cancer progression. To probe this, we have developed and tested a multiparameter cell-surface marker screening pipeline, using flow cytometry to obtain high-resolution systemic leukocyte population profiles that correlate with detection and characterisation of several cancers in murine syngeneic tumour models. We discovered a signature of several blood leukocyte subsets, the most notable of which were monocyte subsets, that could be used to train CATboost ML models to predict the presence and type of cancer present in the animals. Our findings highlight the potential utility of a screening approach to identify robust leukocyte biomarkers for cancer detection and characterization. This pipeline can easily be adapted to screen for cancer specific leukocyte markers from the blood of cancer patient.